1985
DOI: 10.1104/pp.77.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Stress on the Carbohydrate Metabolism of Citrullus lanatus Seeds during Germination

Abstract: Gluconeogenesis in Citrullus lanatus seeds is a post germinative event. Increases in isocitrate lyase activity and incorporation of radioactivity from 12-'4Clacetate into sugars occur only after radicle emergence. During germination, the seeds appear to rely on carbohydrate as the respiratory substrate. At this time, glycolysis, the pentose phosphate pathway, and the tricarbocyclic acid cycle seem to be functional. Utilization of raffinose during germination appears to be important.Water stress, which complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…1), the ratio between the PFP isoforms also changes. These changes coincide with dramatic alterations in the metabolism from a primarily glycolytic function prior to radicle protrusion, to a gluconeogenic function during early seedling growth (10,27), and finally to a photosynthetic function. The highest specific PFP activity in the cotyledons occurs at the peak in gluconeogenesis, which is similar to castor bean endosperm PFP (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1), the ratio between the PFP isoforms also changes. These changes coincide with dramatic alterations in the metabolism from a primarily glycolytic function prior to radicle protrusion, to a gluconeogenic function during early seedling growth (10,27), and finally to a photosynthetic function. The highest specific PFP activity in the cotyledons occurs at the peak in gluconeogenesis, which is similar to castor bean endosperm PFP (21).…”
Section: Discussionmentioning
confidence: 99%
“…Matsumura and Nakai (colocynth or bitter melon) were obtained and stored as previously described (10). The different tissues of C. lanatus plants were obtained from plants grown in a glass house.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barlow (1986) [92] showed that much of the sugar accumulation, which began with the first indication of suppression in leaf elongation under water stress in wheat, was due to glucose, fructose and sucrose. The inhibition of germination of Citrullus lanatus seeds by water stress was investigated by [93], who observed a marked effect on carbohydrate metabolism. Smaller changes in glucose content and in the reducing substance content of the control seeds occurred during germination, coinciding with a decrease in sucrose.…”
Section: Carbohydrates Changes Referencesmentioning
confidence: 99%
“…4e). A similar decrease in fructose has been reported in germinating watermelon seeds, but the mechanism by which this decrease occurs is still unknown [19]. In contrast, in the shoots, the amounts of the three sugars increased significantly from stage 1 to 2 and/or stage 2 to 3 ( Fig.…”
Section: Discussionmentioning
confidence: 56%